...and a tasty answer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Pigs and pig keeping in one form or another can be found almost anywhere in the world. Especially of course in country areas it is common for communities to have pigs rooting and roaming freely around the dwellings, to be brought in one day as househol